Low-Speed Bending Impact Behavior of Adhesively Bonded Single-Lap Joints - Atahan, M. Gokhan; Apalak, M. Kemal; Gokhan Atahan, M.; Kemal Apalak, M. (Taylor & Francis Ltd, 2016)
This study addresses the low-speed impact behavior of adhesively bonded single-lap joints. An explicit dynamic finite element analysis was conducted in order to determine the damage initiation and propagation in the adhesive layers of adhesive single-lap joints under a bending impact load. A cohesive zone model was implemented to predict probable failure initiation and propagation along adhesive-adherend interfaces whereas an elasto-plastic material model was used for the adhesive zone between upper and lower adhesive interfaces as well as the adherends. The effect of the plastic deformation ability of adherend material on the damage mechanism of the adhesive layer was also studied for two aluminum materials Al 2024-T3 and Al 5754-0 having different strength and plastic deformation ability. The effects of impact energy (3 and 11 J) and the overlap length (25 and 40 mm) were also investigated. The predicted contact force-time, contact force-central displacement variations, the damage initiation and propagation mechanism were verified with experimental ones. The SEM and macroscope photographs of the adhesive fracture surfaces were similar to those of the explicit dynamic finite element analysis.
Apalak, Mustafa Kemal/0000-0002-3263-5735; Atahan, Mithat Gokhan/0000-0002-8180-5876
Keywords: Low-Speed Impact; Adhesive Failure; Cohesive Zone Model; Single-Lap Joint; Adhesive Joint